133k views
5 votes
Use the distributive property to solve the equation for x

7(x-2)-3(x+3)=5(x-3)+x

User Zzarbi
by
4.8k points

1 Answer

3 votes

9514 1404 393

Answer:

x = -4

Explanation:

The distributive property is used to eliminate parentheses.

7(x -2) -3(x +3) = 5(x -3) +x . . . . given

7x -14 -3x -9 = 5x -15 +x . . . . . eliminate parentheses

4x -23 = 6x -15 . . . . . . . . . . . collect terms

-8 = 2x . . . . . . . . . . . . . . subtract 4x+15 from both sides

-4 = x . . . . . . . . . . . . divide by 2

__

Check

7(-4 -2) -3(-4 +3) = 5(-4 -3) +(-4)

7(-6) -3(-1) = 5(-7) -4

-42 +3 = -35 -4

-39 = -39 . . . . . answer checks OK

User Shukri Adams
by
5.4k points